Transhumanism and engagement-facilitating technologies in society - Guerreiro, J.; Loureiro, S. M. C.; Romero, J.; Itani, O.; Eloy, S. (Journal of Promotion Management, 2022)
Transhumanism is a movement that explores the possibilities that arise from integrating technology in the human body. Neurostimulators and smart prosthetics are some of the technologies that may soon change the way Humans interact with their surrounding environment and enhance their well-being. The current paper presents a framework for stakeholder well-being through transhumanism and engagement-facilitating technologies on four major blocks, namely: reality-virtuality continuum as stimuli, from stimuli to adoption of transhumanism at individual level, stakeholder engagement and technologies at firm level and stakeholder well-being and technologies. Finally, we propose a future research agenda for exploring such changes in society.